GE_GERICHTE P/2462/2019 vom 21. April 2020 - GE Cour de justice (2020)
LÉSÉ;PARTIE À LA PROCÉDURE;NOTAIRE;VENTE D'IMMEUBLE;AUTORISATION;ASSOCIATION;OBTENTION FRAUDULEUSE D'UNE CONSTATATION FAUSSE | CPP.118; CPP.115; CP.253; CP.317; LDTR